Colombian state subsidies and socioeconomic behavior is generated by access to these (2013)
The Colombian State to the 1991 constitution incorporates social assistance programs and projects and a more equitable distribution of income. Currently with the National Development Plan 2011-2014: Prosperity for All, the State intends to increase the opportunities for improving the quality of life of each of the most vulnerable Colombians municipal, departmental and national level through generating Subsidies greater social convergence.